Introduction to public health - Schneider, Mary-Jane , 1939- (Jones and Bartlett Publishers, 2011)
From the Back Cover: Introduction to Public Health, third edition offers a thorough, accessible overview of the expanding field of public health for students new to its concepts and actors. Written in engaging, nontechnical language, this best-selling text explains in clear terms the multidisciplinary strategies and methods for measuring, assessing, and promoting public health. Packed with illustrative real-world examples, this updated edition provides students with informative discussions of the current technical issues and practical obstacles facing public health practitioners and policymakers alike. Through coverage of new approaches to research and data collection, current best practices in the field, and the social and ethical challenges of devising public policy, Introduction to Public Health, third edition provides readers with a broad-reaching, practical framework for understanding the multifaceted forces and organizations of today's public health enterprise. The Third Edition features: expanded discussions covering a wide variety of current topics, including pandemic flu, poisoning, promotion of physical activity, product contamination, information technology, and health disparities; New discussions regarding U S healthcare reform and the effect of the globalization of national economies on the health of populations; New analysis of public health efforts in the aftermath of Hurricane Katrina; A companion Web site with a complete package of interactive resources for the student (flashcards, glossary, weblinks, matching exercises), as well as downloadable resources for the instructor (TestBank, Instructor's Manual, PowerPoint slides). Visit http://publichealth.jbpub.com/schneider